ORGANIZATION OF CLIENT-SERVER TECHNOLOGICAL ENVIRONMENT IN EDUCATION: ANALYSIS OF IMPACT AND DEVELOPMENT (Scientific journal of the Fergana State University, 2024)
The article examines the impact of the development of digital technologies not only on changing the world around us, but also on the transformation of learning processes and educational systems. Modern education is not limited to the traditional classroom format, and the spread of client-server technology in education opens up new opportunities, eliminating geographical and time restrictions and providing the opportunity to receive an individualized education at a convenient time.